Architecture of Palace-Gardens of Bukhara Emirate Charmgarchorbogh Palace - Абдурахимов Рустам Батиржонович (Scientific Trends, 2024)
In the article, the formation of the geographical location of Charmgarcharbog palace-garden, which was built in the Karmana district of the Navoi region of the Bukhara emirate, and which has now disappeared, the design solution, the creative work of the masters who participated in the construction of the spatial possibilities of the palace and the area around the palace, from the project to its completion, were discussed.
Keywords: Emirate of Bukhara, Karmana, second capital, palace, garden, palace-garden, tannery, tanners' neighborhood, architect, ganchkor, college, plants.